PENELITIAN PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA DAN DAMPAKNYA TERHADAP LINGKUNGAN - Djamin, Martin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Indonesia through government programmes and private sector activities. An assessmentÃ‚Â on performance of photovoltaic systems and study of their impacts was establishedÃ‚Â in Kolaka, South-east Sulawesi. At the moment there are 2270 solar home systemsÃ‚Â (SHS) in this location. During the research and study, there are 9 data loggers haveÃ‚Â been installed in nine solar home systems in 4 villages of Kolaka. These data loggersÃ‚Â were used to monitor and measure some parameters such as solar insolation , VBattery,VLoad, ILoad, IModule, and room temperature. Besides performance data collection above, aÃ‚Â quantitative research method was done to explore the quality of life of rural and remotepeoples. 175 questionnaires were used to collect the data from households in 4 villagesÃ‚Â Polinggona, Popalia, Petudua dan Pewisoa Jaya. This paper will discuss resuts of theÃ‚Â measurement of solar home systems, the impact on daily life of villagers and globalÃ‚Â and local environmental impact of the use of solar home systems.Kata Kunci: PLTS, data-logger, alat pengontrol baterai